ANALYSIS OF EMPLOYEE INVOLVEMENT IN THE WORKS AT SLEMAN DISTRICT HEALTH OFFICE - Suyati, Suyati (Management, 2010)
Sleman District Health Office in charge of as many as 25 health centers UPTD. The number of employees in the Sleman district health offices as many as 101 people. Of functions and tasks performed by the office of Sleman District Health Office, the role of civil servants is very important. Obstacles in the Sleman district health development is not yet maximal employees in providing services. This makes the planning of programs and decisions, not based on accurate information (not evidence based). The effectiveness of the organization is heavily influenced by the effectiveness of individuals, so that the low performance of employees also affect the poor performance of the health department in keseluruhan.Penilaian employee performance according to the Ministry of Health of the Republic of Indonesia in 2000 is a tool that fosters the motivation to grow and improve the performance of which is less by showing his best. Therefore, the need for research on the Involvement of Employees Working in Sleman District Health Office. The size of the study concluded the involvement of employees in completing the work in Sleman District Health Office average height when seen from the analysis that there were 33 respondents from 40 respondents or 82.5%.